The input of resolution A/RES/S-30/1 in the formation of the new global anti-drug approaches - Eremin, A.A.; Eremina, M.S.; Abdurashitova, E.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
The problem with proliferation of illicit narcotic and psychotropic substances has existed for as long as the humanity itself. However only relatively recently it has evolved into an international issue. It is hard to argue that the world drug problem cannot be solved only by the efforts of just one country. For these reasons international community has united their efforts in order to effectively deal with the problem of drugs that is not limited by certain country or region. One of the most important mechanisms of effort coordination against the drug traffic on the international level is the United Nations. The modern developments in the sphere of finding proper ways of combating illicit drug trade have shown that the international community tends to believe that drugs do not only damage the health of users, but provide a wide variety of social, economic and security risks. Keeping that in mind, the importance of the recently adopted resolution of the UN General Assembly on the issue of drugs is obvious and demonstrates high interest of the World in forming a balanced and effective way to fight the illicit drug trade. Most recent United Nations resolution A/RES/S-30/1 thus poses an immediate scientific interest in terms of researching the potential of the global anti-drug efforts. The article also critically assesses the current approaches towards combating illicit drugs, among which are the traditional coercive approaches of the War on Drugs and various “zero tolerance” policies.